The Relationship Between Early Pregnancy, Birth Distance, and Resident Status with Stunting Incidence in Elementary School Children In Enrekang Rural - Abri, Nur; Zakiah, Nur; Risal, Alya Fajrani (Journal of Health and Nutrition Research, 2023)
This study aims to determine the relationship between maternal age at first pregnancy, birth spacing, and residence status with the incidence of stunting in elementary school children in rural Enrekang. A community-based cross-sectional study was conducted in 3 villages in Enrekang Regency. This study involved 100 elementary school children who were selected by purposive sampling. Data was collected using a validated structured questionnaire and microtia. These results are then processed to obtain the child's nutritional status using the WHO Anthro-Plus software, namely Z-score the Height/Age index. The statistical test used is the Chi-square test. From a total of 100 children as respondents, 72.0% were found to be stunted and 28.0% were found to be normal. The age of the mother during pregnancy is considered ideal at 62.0%, the ideal birth spacing for children is 84.0%, and the status of residence with own ownership is 67.0%. The results showed that there was no significant relationship between the mother's age at first pregnancy (p=0.693) and birth spacing (p=0.373) and the incidence of stunting. Meanwhile, the status of residence is considered related to the incidence of stunting in elementary school children with a value of p = 0.014. Maternal age at first pregnancy and birth spacing were not related to stunting. We suspect parenting style, the mother's attitude, sanitation hygiene, environmental cleanliness, and housing conditions indirectly contribute to the incidence of stunting. It is hoped that further research examines this matter.